JURIDICIAL REVIEW OF THE FOREIGNERS INVOLVED IN CRIMINAL ACTIONS OF PEOPLE SMUGGLING AND TAKE COVER BEHIND THE RIGHTS - Achmad Setiawan S (Polteknik Imigrasi, 2019)
This paper provides an understanding of the aspects that need to be considered in handling people smuggling in Indonesia. Indonesia became a country that ratified the UN Convention against transnational crime in 2000. One of the articles that regulates migrants who are considered victims of smuggling cannot be subject to criminal responsibility. So that some examples of people smuggling cases that have occurred in Indonesia, the foreigners involved are considered victims and can feel safe from criminal sanctions. Not a few of them are applying for refugee status to be able to remain in Indonesian territory. This seems to legitimize the entry of illegal immigrants into Indonesian territory, because as is well known, in general, their entry into Indonesian territory is not accompanied by legal documents and does not go through immigration checks. Although Indonesia is a country that has not ratified the Refugee Convention, the issuance of Perpres 125 of 2016 is a gap for these immigrants to get asylum rights in Indonesia. In addition, several factors underlying the occurrence of criminal people smuggling will also be discussed in this paper.